The Influence of Experience in the Modeling of Social Representations of the Family-School Relationship in Rural Educational Institutions in the Ñuble Region, Chile - Cárcamo-Vásquez, Héctor; Méndez-Bustos, Pablo (Revista Electrónica Educare, 2019)
This work presents the influence of agents’ experience in modeling the representation they have of the family-school relationship in the rural context. The objective of the study is to recognize the social representations that teachers and families have regarding the family-school relationship. The methodology used corresponds to the qualitative design through the case study method; the data processing technique is the semi-structured interview. The research was conducted in 10 rural schools belonging to the Ñuble Region, Chile. A total of 16 teachers and 36 parents were interviewed, and the data was analyzed through semantic analysis. The results showed that the life experience of the agents influences the representation they have about the family-school relationship and the role each agent involved attributes to it. From the teaching staff, a distinction can be seen between the conceptions derived from the teaching experience, personal experiences, and the complete knowledge of the context. For their part, families recognize the influence of experience derived from the family life cycle, differentiating between first-time parents and those who are even responsible for the care of grandchildren. In conclusion, the influence of experience, as a modeler of the representations that teachers and families have regarding the family-school relationship and the role each subject has, comes from the confluence of the multiple experiences lived by the agents interviewed.